Enzyme-triggered deshielding of nanoparticles and positive-charge mediated lysosomal escape for chemo/photo-combination therapy. Issue 31 (25th July 2019) - Zhang, X. Q.; Cai, S. S.; He, Y. M.; Zhang, M.; Cao, J.; Mei, H.; Li, S.; He, B.
Abstract : Smart nanoparticles with active-targeting, enzyme-triggered deshielding and positive-charge characteristics were fabricated for efficient chemo/photo-combination therapy. Abstract : An all in one nano-system with active-targeting, enzyme-triggered deshielding and positive-charge characteristics was fabricated for chemo/photo-combination therapy to allow efficient tumor targeting, cellular internalization and lysosomal escape. The deshielding of NPs was induced by enzyme triggered degradation of the NP shell, and consequently exposure of the positively charged core accelerates escape of NPs from the lysosome to exert anticancer effects with high efficiency.